Whitehead's religious thought: from mechanism to organism, from force to persuasion - Dombrowski, Daniel A. (State University of New York, 2017)
Griffin's panexperientialism as perennial philosophy -- Stengers on Whitehead on God -- Rawlsian political liberalism and process thought -- Hartshorne, the process concept of God, and pacifism -- Butler and grievable lives -- Wordsworth, Whitehead, and the romantic reaction